Professional integration between specialists and non-specialists in teaching Arabic to non-native speakers: An analytical study in light of modern educational literature (The International Journal for Scientific Research, 2025)
With the global expansion of teaching Arabic to non-native speakers, the participation of teachers from non-specialized academic backgrounds has become a pressing issue. This raises critical questions about professional competence, legitimacy, and the impact on the quality of learning outcomes (Al-Qudah, 2018). This paper aims to analyze this phenomenon from an educational perspective by reviewing the relevant literature (Krashen, 1982; Omari, 2016), examining the realities of the field, and proposing an integrative model that acknowledges the unique nature of Arabic language instruction for non-native speakers. The paper is based on the hypothesis that the quality of Arabic language teaching does not rely solely on academic specialization, but rather on a combination of pedagogical training, classroom experience, and institutional support (Nation & Newton, 2009). The study recommends setting clear standards for qualifying non-specialist teachers and emphasizes the role of universities in providing academic supervision in this growing field.
Keywords: Teaching Arabic; Non-Specialist Teachers; Teaching Competence; Second Language Instruction; Teacher Training; Professional Integration